An introduction to the theory of OBCI-algebras - Eunsuk Yang; Eun Hwan Roh; Young Bae Jun (AIMS Mathematics)
The purpose of this paper was to introduce the concept of 'OBCI-algebras' as a partially ordered generalization of BCI-algebras. The notion of OBCI-algebras was introduced, and related properties were investigated. The notions of OBCI-subalgebras and (closed) OBCI-filters of OBCI-algebras were defined and the relationship between the OBCI-subalgebras and OBCI-filters was discussed. In addition, the direct product OBCI-algebra was discussed, and the OBCI-filter related to it was also addressed.